The Anti-Coal and Anti-Coal Seam Gas Campaigns as Components of the Climate Movement in Australia: Responses to Corporate Hegemony. Issue 1 (2nd January 2021) - Baer, Hans A.; Singer, Merrill
ABSTRACT: In this paper we examine the climate-driven anti-coal and anti-coal gas organizations and activist campaigns in Australia, a country that is a major force in global coal production and trade, and a growing coal seam gas producer and exporter. The sociopolitical context for our analysis is the close nexus that has existed historically between the coal industry and the Australian state, as well the more recent relationship between the state and the burgeoning coal seam gas industry. We review an array of major anti-coal groups in Australia and assess not only their protest activities but – to the degree they have articulated them – their respective stances on climate justice and on capitalism as a primary driver of climate injustice. While a few groups within the anti-coal movement tend to be anti-capitalist in their orientation, most advocate a largely green social democratic position which calls for ecological modernization as a major climate change mitigation strategy, without addressing whether this is achievable within the current globally dominant political economy.